From enemy to brother: the revolution in Catholic teaching on the Jews ; 1933 - 1965 - Connelly, John (Harvard Univ. Press, 2012)
The problem of Catholic racism -- The race question -- German volk and Christian reich -- Catholics against racism and antisemitism -- Conspiring to make the Vatican speak -- Conversion in the shadow of Auschwitz -- Who are the Jews? -- The Second Vatican Council -- A particular mission for the Jews